Supervisión de estudiantes de Enfermería - Llivi Ruilova, Danny Vicente (2023)
The supervision of Nursing students from the Faculty of Health and Human Sciences of the UEB was successfully carried out, the same ones who are doing their Rotating Internship, in the care units, such as the Riobamba General Teaching Hospital and the General Hospital. Latacunga.